2013
DOI: 10.1002/ijc.28107
|View full text |Cite
|
Sign up to set email alerts
|

Marriage, cohabitation and incidence trends of invasive penile squamous cell carcinoma in Denmark 1978–2010

Abstract: Few population-based studies have investigated the relation between living arrangements and risk of invasive penile squamous cell carcinoma (iP-SCC). Using long-term national cancer registry data in Denmark we examined incidence trends of iP-SCC. Furthermore, we examined the relation between marital status, cohabitation status and risk of iP-SCC using hazard ratios (HRs) with 95% confidence intervals (CIs) obtained in Cox proportional hazards regression analyses as our measure of relative risk. Overall, 1,292 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 32 publications
2
13
0
Order By: Relevance
“…A similar association was found in a USA register‐based study . Furthermore, a Danish population‐based study encompassing 1292 men with penile cancer found that all categories of single men (unmarried, divorced, widowers) were at an increased risk of invasive penile cancer . This also applies to other malignancies, e.g.…”
Section: Discussionsupporting
confidence: 80%
“…A similar association was found in a USA register‐based study . Furthermore, a Danish population‐based study encompassing 1292 men with penile cancer found that all categories of single men (unmarried, divorced, widowers) were at an increased risk of invasive penile cancer . This also applies to other malignancies, e.g.…”
Section: Discussionsupporting
confidence: 80%
“…The number of lifetime partners consistently proved to be correlated with a higher risk of pSCC both in a case-control study based on telephone interviews and in a population-based registry study [11,14].…”
Section: Epidemiologymentioning
confidence: 95%
“…In a population-based study, Ulff-Møller et al found that men who were unmarried, divorced or widowed were at increased risk of invasive penile squamous cell carcinoma (pSCC) [11]. The number of lifetime partners consistently proved to be correlated with a higher risk of pSCC both in a case-control study based on telephone interviews and in a population-based registry study [11,14].…”
Section: Epidemiologymentioning
confidence: 97%
See 1 more Smart Citation
“…The incidence in Denmark is estimated to be 0.8/100,000 population/year, and the mean age at diagnosis is 65 years 4. Data on ∼65 patients are entered into the database each year, which has currently accumulated to more than 200 entries.…”
Section: Study Populationmentioning
confidence: 99%